Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.4049/jimmunol.176.6.3507
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of Glucocorticoid-Induced TNF Receptor Costimulates NKT Cell Activation In Vitro and In Vivo

Abstract: Glucocorticoid-induced TNF receptor (GITR) is known to provide costimulatory signals to CD4+CD25− and CD4+CD25+ T cells during immune responses in vivo. However, the functional roles of GITR expressed on NKT cells have not been well characterized. In this study, we have explored the functions of GITR as a costimulatory factor on NKT cells. GITR was found to be constitutively expressed on NKT cells and its expression was enhanced by TCR signals. GITR engagement using DTA-1, an agonistic mAb against GITR, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 51 publications
0
40
1
Order By: Relevance
“…Therefore, we tested two co-stimulatory molecules -GITR and ICOSL -that can potentially shape NKT-cell responses. GITR had been shown previously to be essential for activation of NKT cells [18], while ICOSL can stimulate CD41 T cells to secrete IL-4 rather than 31].When a blocking anti-GITR antibody was added to the co-cultures of NKT cells with either MZ B cells or cDCs sensitized by aGalCer, NKT-cell proliferation and IL-4 production were not inhibited ( Fig. 6A and C).…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…Therefore, we tested two co-stimulatory molecules -GITR and ICOSL -that can potentially shape NKT-cell responses. GITR had been shown previously to be essential for activation of NKT cells [18], while ICOSL can stimulate CD41 T cells to secrete IL-4 rather than 31].When a blocking anti-GITR antibody was added to the co-cultures of NKT cells with either MZ B cells or cDCs sensitized by aGalCer, NKT-cell proliferation and IL-4 production were not inhibited ( Fig. 6A and C).…”
mentioning
confidence: 84%
“…Some studies showed that engagement of GITR leads to co-stimulation of NKT cells and increases production of IFN-g and IL-4 [18]. In contrast, others demonstrated that GITR engagement elicits co-inhibitory activity for antigen-induced NKT cells [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations